Economic characteristic of sport clubs in the Czech republic - Marek Pavlík (Palacký University Olomouc, 2013)
BACKGROUND: The economic situation and other characteristic of sport clubs are quite unrevealed in the Czech Republic. The sport is traditionally one of activities supported by the public sector; however we know surprisingly little about sport clubs as recipients of this support. We emphasize the municipality level because public authorities are the most typical partners for sport clubs. AIMS: The aim of this research was to reveal the economic situation of sport clubs and gather data about their cooperation with municipalities. METHODOLOGY: We present results of a questionnaire which was completed during spring 2011. We address 1,567 sport clubs and received 430 question-form filled. RESULTS: We found that the economic situation of sport clubs is quite poor, but it cannot be proved as a result of insufficient support from public resources. As the key variable for the quality of relationship between sport clubs and municipalities as well as the grants strategy were proved by the number of inhabitants. We set a necessity of future research especially at the field of analysis of impact grants policy. CONCLUSION: We proved that most municipalities prefer an allocation of a lower sum of funds than it was asked. Short term impacts can be positive - more applicants are satisfied but there is a risk of "inflation" of a grant request in the long term view. Applicants will anticipate the cut, and they will ask for more money. It could cause the pressure on public budgets and the illusion of the lack of funds.